CARRYING CAPACITY SERVICES BASED ON CLEAN WATER SUPPLY ECOSYSTEM IN SOUTH TAPANULI DISTRICT - Ambosa Hidayat; Rifardi Rifardi; Suwondo Suwondo (Fakultas Perikanan dan Kelautan, Universitas Riau, 2020)
Environmental carrying capacity with the other methods has been used by other countries especially developed countries. One of method was based on ecosystem services which developed by MEA in 2005. This approach looked environmental carrying capacity through benefits that people could get on it. In the other hand, environmental carrying capacity based on ecosystem service could integrated in spatial urban regional planning or other developing plan. Ecosystem services are benefits that humans getfrom ecosystems. Sustainable development era has increased demand on ecosystem services information to be incorporated into various development policies and planning. This research Purpose to assessing spatial distribution of ecosystem services for clean water supply as basis of management for sustainable resources. The research method was an ecosystem service approach using two estimating variables, land cover and ecoregion as the landscape ecosystem. Each estimator variables assessed of Ecosystem services by expert judgment with coefficient values. This research specifically discusses the comparison of the results of maps of ecosystem services formulated through experts' judgement on land use based proxy and a combination of land cover and ecoregion. We use Analytical Hierarchy Process (AHP) with pairwise comparison method to asssess the potential of ecosystem services from land cover and ecoregion. The case study area is south tapanuli district, while the type of ecosystem services analyzed is type of clean water supply. The results of the calculations show that the index of ecosystem services resulting from acombination of land cover and ecoregion produces a more accurate map of ecosystem services with qualitative information. The coefficient values were processed and analyzed by using GIS technique to produces spatial distribution of Ecosystem Services values which were divided into five classes of the ecosystem services : very high, high, medium, low, and very low. The results showed that south tapanuli district have great potentials to provider the ecosystem services for clean water supply with medium to very high class value of ecosystem services (36,17% of the South Tapanuli District).